Respuesta :

Answer:

Option B

Step-by-step explanation:

If you replace the X in the P(X) it becomes -1 and then you'll change every x in the equation to -1

2(-1)³ + 2(-1)² -3(-1) -3

which = -2 +2 +3 -3

= 0

Since the answer is 0 it means x + 1 is a factor of 2x³ + 2x² - 3x -3

Answer:

  • B. x + 1

-----------------------

Factorize the given polynomial:

  • P(x) =
  • 2x³ + 2x² - 3x - 3 =
  • 2x²(x + 1) - 3(x + 1) =
  • (x + 1)(2x² - 3)

As we see the polynomial is divisible by x + 1.

Correct choice is B.